Fasting in Islam: A combination of spiritual elevation and prevention of diseases - Khattak, Muhammad Muzaffar Ali Khan; Mohamed Nor, Noraishah; Mamat, Nik Mazlan; Mohd Shukri, Nor Azwani; Mohd Abu Bakar, Wan Azdie (2016)
The obligatory fasting of Ramadan is not only an Islamic ritual to enhance the God-consciousness (called Taqwa), it may also lead to improvement of health status of fasting person. In other words, it is a complete overhauling instrument of Muslims soul/body in terms of faith and health. This can be termed as “Islamic fasting: a combination of spiritual elevation and prevention of diseases”. Fasting plays an important role in the improvement of hyperlipidemia, obesity (fat loss), diabetes, cognition, cell functions, immunological factors, inflammation, stress and lifespan etc. This article is an effort to review and discuss research carried out during the holy month of Ramadan on various aspects of human health.